Deteksi Fraud di Era Revolusi Industri 4.0 Sebuah Analisis Kritis - Irmawati, Irmawati; Sumardi, Sumardi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2023)
This study aims for analyze in a manner critical related detection fraud. Method used is with do study library. Results study This show that globalization No only impact phenomenon on field technology course , however has disrupt various other fields like social, legal, and economy. Consequences from disruption This make order world changed drastic. Revolution Industry 4.0 regarding fraud detection in this case is not Possible only faced with development technology without involve dynamics social in it. Besides prepare Power superior competitiveness, necessary built awareness And maturity public in address development world moment this, especially in the age post truth, when flowing information swift without clarity the truth.